2019
DOI: 10.1142/s0219477519500111
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Fluctuations in Mesoscopic Simulations of Nematic Liquid Crystals

Abstract: We analyzed hydrodynamic fluctuations in nematic liquid crystals simulated by Multi-particle Collision Dynamics. Velocity effects on orientation were incorporated by allowing mesoscopic velocity gradients to exert torques on nematic particles. Backflow was included through an explicit application of angular momentum conservation during the collision events. We measured the spectra of hydrodynamic fluctuations and compared them with those derived from a linearized hydrodynamic scheme. Numerical results were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Specifically [ 48 ], which yields . It is worth noticing that due to their anisotropic character, actual nematic solvents have more than one viscosity coefficient, whereas N-MPCD approximates the momentum transport through the solvent as isotropic [ 55 ]. However, this approximation has shown consistent results for simulations of CPs driven by nematic flow [ 29 , 36 ] and can be considered as a first attempt to reproduce the hydrodynamic behaviour on the mesoscopic scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically [ 48 ], which yields . It is worth noticing that due to their anisotropic character, actual nematic solvents have more than one viscosity coefficient, whereas N-MPCD approximates the momentum transport through the solvent as isotropic [ 55 ]. However, this approximation has shown consistent results for simulations of CPs driven by nematic flow [ 29 , 36 ] and can be considered as a first attempt to reproduce the hydrodynamic behaviour on the mesoscopic scale.…”
Section: Resultsmentioning
confidence: 99%
“… is the ratio of viscous-to-elastic effects and is customarily defined as where is a rotational viscosity and ( ) is a characteristic velocity (length). The ratio can be estimated from the spectrum of director fluctuations as discussed in References [ 55 , 61 ]. Using the same set of MPCD parameters as here but with , it is obtained [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical experiments were conducted using the same simulation parameters ∆t, k B T, m,N c , a, and L, given in section 3.2. Nematic order was simulated using U = 20k B T. For this mean-field strength, it has been shown that the average scalar order parameter produced in collision cells,S c = 0.947, is in agreement with predictions of self-consistent models of NLCs [32]. Two main features of hydrodynamic correlation functions in MPCD-N will be explored.…”
Section: Measurementsmentioning
confidence: 91%
“…Dynamic equations for director fluctuations can be obtained by replacing equations (3.11) and (5.1) into equations (5.2) and (5.4), and retaining only linear contributions. In a first approximation, mass and momentum transport can be assumed to be still given by equations (3.1) and (3.2), thus neglecting the effects of backflow [32]. In section 5.1, the validity of this assumption will be explored.…”
Section: Fluctuating Nematodynamicsmentioning
confidence: 99%